The Impact of COVID-19 on Women’s Health in Nepal - Poudel, R.; Dangal, G.; Caagbay, D. (Kathmandu University Medical Journal, 2020)
COVID-19 has significantly impacted the world and Nepal is no exception. The pandemic has caused a reduction in health service delivery, especially for women’s health conditions, resulting in an increase in challenges for an already vulnerable group. Maternity care, reproductive health services, preventive interventions, nutritional advice and mental health care are not being addressed and with an increase in domestic violence, the health and wellbeing of women in Nepal is precarious and needs to be addressed immediately.